Analisis Dampak Investasi Energi Terbarukan Terhadap Pertumbuhan Ekonomi Indonesia dan Implikasinya Bagi Pembangunan Berkelanjutan - Rizka Amalia Putri (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2026)
The transition toward renewable energy has emerged as a fundamental strategic response to mitigate the adverse effects of global climate change and to fulfill the urgent demand for sustainable energy systems worldwide. This study aims to empirically analyze the impact of renewable energy investment on economic growth in Indonesia. To achieve this objective, a quantitative approach is employed using a simple linear regression model. The analysis utilizes annual time series data spanning a fifteen-year period from 2010 to 2024. Within this empirical framework, the total installed capacity of renewable energy power plants is utilized as a measurable proxy for green investment, while the Gross Domestic Product (GDP) serves as the primary indicator of economic growth. The statistical estimation results demonstrate that an increase in the installed capacity of renewable energy significantly and positively affects the national GDP. These findings indicate that capital allocation toward green energy infrastructure does not hinder economic expansion but rather acts as a catalyst for value creation. Consequently, the study highlights the critical importance of formulating integrated governmental policies and providing targeted investment incentives. Such structural interventions are essential to accelerate an inclusive national energy transition, attract broader private sector participation, and ultimately ensure long-term sustainable economic development in Indonesia.